PENGARUH REKRUTMEN, SELEKSI, DAN AKTUALISASI DIRI TERHADAP KINERJA KARYAWAN PT. EXEL MANDIRI INOVASI - Delvia Rahman W.S; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT The research is conducted at PT. Exel Mandiri Inovasition’s. The aim of this research is to examine and analyze the influences of Recruitment, Selection and Self Actualization toward Employee’s Performance partially or simultaneously, and examine and analyze the dominant influences of recruitment, selection and self-actualization toward employee’sperformance. The variables used in this research are Recruitment, Selection and Self Actualization as independent variables and employee’s performance as the dependent variable. The type of research used is explanatory research. The samples used are 74 respondents of using saturated sample method. The data collection method used is questionnaire method. The analysis methods used areinstrument test, normality test, classic assumption test, linear multiple regression test,and hypothesis test with the help of SPSS 14.0 for Windows. The results of the research show that Recruitment has a significant influence on the performance of PT. Exel Mandiri Innovation’s employees, Selection has a significant influence on the performance of PT. Exel Mandiri Innovation’s employees, Self Actualization has a significant influence on the performance of PT. Exel Mandiri Innovation’s employees. Therefore, it can be concluded that Recruitment, Selection and Self Actualization partially or simultaneously have significant influences on the performance of PT. Exel Mandiri Innovation’s employees..Keywords:Rcruitmen, Selection, Self Actualization, Employee performance.